Lithium doped calcium phosphate cement maintains physical mechanical properties and promotes osteoblast proliferation and differentiation. Issue 5 (9th February 2016) - Li, Li; Wang, Renchong; Li, Baichuan; Liang, Wei; Pan, Haobo; Cui, Xu; Tang, Jingli; Li, Bing
Abstract: Calcium phosphate cement (CPC) has been widely used in bone tissue repairing due to its physical mechanical properties and biocompatibility. Addition of trace element to CPC has shown promising evidence to improve the physical properties and biological activities of CPC. Lithium (Li) has effect on osteoblast proliferation and differentiation. In this study, we incorporated Li to CPC and examined the physical properties of Li/CPC and its effect on osteoblast proliferation and differentiation. We found that Li doped CPC maintained similar setting time, pore size distribution, compressive strength, composition, and morphology as CPC without Li. Additionally, Li doped CPC improved osteoblast proliferation and differentiation significantly compared to CPC without Li. To our knowledge, our results, for the first time, show that Li doped CPC has beneficial effect on osteoblast in cell culture while keeps the excellent physical–mechanical properties of CPC. This study will lead to potential application of Li doped CPC in bone tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 944–952, 2017.